Comparative Phosphoproteomic Analysis under High-Nitrogen Fertilizer Reveals Central Phosphoproteins Promoting Wheat Grain Starch and Protein Synthesis - Zhen, Shoumin; Deng, Xiong; Zhang, Ming; Zhu, Gengrui; Lv, Dongwen; Wang, Yaping; Zhu, Dong; Yan, Yueming (Frontiers in Plant Science, 2017)
Nitrogen (N) is a macronutrient important for plant growth and development. It also strongly influences starch and protein synthesis, closely related to grain yield and quality. We performed the first comparative phosphoproteomic analysis of developing wheat grains in response to high-N fertilizer. Physiological and biochemical analyses showed that application of high-N fertilizer resulted in significant increases in leaf length and area, chlorophyll content, the activity of key enzymes in leaves such as nitrate reductase (NR), and in grains such as sucrose phosphate synthase (SPS), sucrose synthase (SuSy) and ADP glucose pyrophosphorylase (AGPase). This enhanced enzyme activity led to significant improvements in starch content, grain yield and, ultimately, bread making quality. Comparative phosphoproteomic analysis of developing grains under the application of high-N fertilizer performed 15 and 25 days post-anthesis identified 2470 phosphosites among 1372 phosphoproteins, of which 411 unique proteins displayed significant changes in phosphorylation level (> 2-fold or < 0.5-fold). These phosphoproteins are involved mainly in signaling transduction, starch synthesis, energy metabolism. Pro-Q diamond staining and Western blotting confirmed our phosphoproteomic results. We propose a putative pathway to elucidate the important roles of the central phosphoproteins regulating grain starch and protein synthesis. Our results provide new insights into the molecular mechanisms of protein phosphorylation modifications involved in grain development, yield and quality formation.